2001
DOI: 10.1093/embo-reports/kve184
|View full text |Cite
|
Sign up to set email alerts
|

A protein–protein interaction map of the Caenorhabditis elegans 26S proteasome

Abstract: The ubiquitin-proteasome proteolytic pathway is pivotal in most biological processes. Despite a great level of information available for the eukaryotic 26S proteasome-the protease responsible for the degradation of ubiquitylated proteinsseveral structural and functional questions remain unanswered. To gain more insight into the assembly and function of the metazoan 26S proteasome, a two-hybrid-based protein interaction map was generated using 30 Caenorhabditis elegans proteasome subunits. The results recapitul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 29 publications
5
111
1
Order By: Relevance
“…In various systems, RPN-12 has been shown to function in the regulatory particle of the proteasome and was proposed to share some activities with the subunit RPN-10 ( Wilkinson et al 2000;Glickman and Ciechanover 2002;Takahashi et al 2002). In C. elegans, only 3 of the 30 genes shown so far to encode proteasome subunits (Davy et al 2001) do not result in embryonic lethality upon disruption by RNAi: rpn-9, rpn-10, and rpn-12 (Takahashiet al 2002;Kamath et al 2003;Sonnichsen et al 2005). While we did not identify rpn-9 or rpn-10 in the genomewide screen, subsequent analysis revealed that RNAi from either of these two genes can also suppress par-2(it5ts) embryonic lethality (Table 1), albeit less efficiently than RNAi from rpn-12.…”
Section: Resultsmentioning
confidence: 99%
“…In various systems, RPN-12 has been shown to function in the regulatory particle of the proteasome and was proposed to share some activities with the subunit RPN-10 ( Wilkinson et al 2000;Glickman and Ciechanover 2002;Takahashi et al 2002). In C. elegans, only 3 of the 30 genes shown so far to encode proteasome subunits (Davy et al 2001) do not result in embryonic lethality upon disruption by RNAi: rpn-9, rpn-10, and rpn-12 (Takahashiet al 2002;Kamath et al 2003;Sonnichsen et al 2005). While we did not identify rpn-9 or rpn-10 in the genomewide screen, subsequent analysis revealed that RNAi from either of these two genes can also suppress par-2(it5ts) embryonic lethality (Table 1), albeit less efficiently than RNAi from rpn-12.…”
Section: Resultsmentioning
confidence: 99%
“…To date, we do not know whether this rapid turnover is inherent to the protein or involves specific degradation mechanisms. One interesting hint for this question is that the homologue of Nsa2 in Caenorhabditis elegans (Q9XTD3) interacts in two-hybrid with the Rpn10 subunit of the proteasome (20). Hence, when pre-60 S biogenesis is impaired, Nsa2 might be targeted to the proteasome degradation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Like TRC8, Hrd1/der3p is a multi-membrane spanning ER resident protein containing a RING-H2 ®nger with E3-ubiquitin ligase activity (Deak and Wolf, 2001;Bays et al, 2001). Using a yeast 2-hybrid screen, Hrd1/der3p was found to interact with the proteasome lid subunit, Rpn11 (Davy et al, 2001), which is the direct counterpart to JAB1 (Voges et al, 1999). This suggests that TRC8 may be somewhat analogous to the Hrd1/der3p protein complex in the ER, perhaps targeting a subset of proteins for degradation in a VHL-dependent manner.…”
Section: Discussionmentioning
confidence: 99%